The Effectiveness of Mindfulness-Based Cognitive Therapy on Social Anxiety and Emotional Regulation in Adolescents of Divorced Families - Arab , Mobina; Abolfathi Doyran , Leila; Oboori, Masoumeh; Rajabi , Maedeh; Khaefi, Azita (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to determine the effectiveness of mindfulness-based cognitive therapy on social anxiety and emotional regulation among adolescents from divorced families. Methods and Materials: The present research employed a quasi-experimental design with a pretest–posttest format and a control group. The statistical population consisted of adolescents from divorced families who referred to psychological counseling centers in Tehran in 2026. Using convenience sampling, 30 participants were selected and randomly assigned into an experimental group (n = 15) and a control group (n = 15). Data collection instruments included the Social Anxiety Scale for Adolescents and the Cognitive Emotion Regulation Questionnaire. The experimental group received eight 2-hour sessions of mindfulness-based cognitive therapy, whereas the control group did not receive any intervention. Data were analyzed using descriptive statistics and analysis of covariance (ANCOVA) through SPSS software. Findings: The findings revealed that mindfulness-based cognitive therapy had a significant effect on reducing social anxiety among adolescents from divorced families (F = 46.68, p < 0.001, η² = 0.61). In addition, the intervention significantly improved emotional regulation in the experimental group compared with the control group (F = 28.32, p < 0.001, η² = 0.67). The results indicated that after controlling for pretest scores, the differences between the experimental and control groups in posttest scores were statistically significant, demonstrating the effectiveness of mindfulness-based cognitive therapy on both dependent variables. Conclusion: The findings of the present study suggest that mindfulness-based cognitive therapy is an effective psychological intervention for reducing social anxiety and improving emotional regulation among adolescents from divorced families. By enhancing self-awareness, emotional acceptance, and adaptive coping strategies, mindfulness-based cognitive therapy may contribute to better psychological adjustment and emotional functioning in vulnerable adolescents.